THE EFFECT OF TASK GROUP COUNSELING ON STUDENT RESILIENCE - Rena Madina; Nella Dasinsingon (International Journal of Innovations in Engineering Research and Technology, 2020)
This research is motivated by the symptoms that occur in MTS Negeri I Gorontalo City, namely the low resilience of grade V III students. The purpose of this study was carried out to determine the effect of task group guidance on student resilience. From the research results, it was found that generally the resilience of grade VIII students was in the low category. This research is a quasi-experimental research using the research design "one group pre-test and post-test design. This study consists of two variables, namely variable X ( Task Group Guidance ) and Variable Y (Resilience) class VIII MTS Negeri I Gorontalo City. The population in this study amounted to 391 students. This study was given for 8 treatments to a sample of 15 students. The sampling technique used was purposive sampling, which is a sampling technique with certain considerations. The data collection technique is in the form of a questionnaire technique about the variable Y (student resilience) . The results showed that the pre-test mean score was 170.07 and the post- test mean score was 197.73. The results of hypothesis testing obtained tcount> ttable, namely 4.546> 1, 76. It can be concluded that the hypothesis in this study is that there is an effect of task group guidance on resilience in class VIII students at MTS Negeri I Gorontalo City .